Chemical compositions, larvicidal and antimicrobial activities of Zingiber castaneum (Škorničk. & Q.B. Nguyễn) and Zingiber nitens (M.F. Newman) essential oils - Le Thi Huong; Trinh Thi Huong; Nguyen Thi Bich; Isiaka Ajani Ogunwande (Universidade de São Paulo, 2023)
Abstract In this paper, the chemical constituents, larvicidal and antimicrobial activities of hydrodistilled essential oils from Zingiber castaneum Škorničk. & Q.B. Nguyễn and Zingiber nitens M.F. Newman were reported. The main constituents of Z. castaneum leaf were bicyclogermacrene (24.8%), germacrene D (12.9%), cis-β-elemene (11.2%) and β-pinene (10.3%), while sabinene (22.9%) and camphene (21.2%) were the significant compounds in the rhizome. However, the dominant compounds in the leaf of Z. nitens includes β-pinene (45.8%) and α-pinene (10.7%). Terpinen-4-ol (77.9%) was the most abundant compound of the rhizome. Z. castaneum rhizome oil displayed larvicidal activity against Aedes aegypti and Culex quinquefasciatus with LC50 values of 121.43 and 88.86 µg/mL, respectively, at 24 h. The leaf oil exhibited activity with LC50 values of 39.30 µg/mL and 84.97 µg/mL, respectively. Also, the leaf and rhizome oils of Z. nitens displayed greater larvicidal action towards Ae. aegypti with LC50 values of 17.58 µg/mL and 29.60 µg/mL, respectively. Only the rhizome oil displayed toxicity against Cx. quinquefasciatus with LC50 value of 64.18 µg/mL. All the studied essential oils inhibited the growth of Pseudomonas aeruginosa ATCC25923 with minimum inhibitory concentration (MIC) value of 50.0 µg/mL. This paper provides information on the larvicidal and antimicrobial potentials of Z. castaneum and Z. nitens essential oils.